PADDLE BALL AS POLITICS GENDER AND THE ROLE OF SOCIABILITY IN THE 1960S UNITED STATES CONGRESS - Pierce, Rachel (Temp - tidsskrift for historie, 2014)
ABSTRACT Paddle Ball as Politics: The Role of Sociability in the United States Congress in the Sixties Scholars have traditionally approached the legislative process as a systematic weighing and balancing constituency desires, party loyalties, ideological beliefs, and national goals. However, legislatures do not make their decisions in a vacuum, and the individuals who constitute a legislature remain subject to the ever-changing traditions and social norms that govern behavior in the Capitol. Congress was constantly made and remade through the repetition of gendered behaviors, traditions, and systematized rhetoric. The prevalence of male-only activities increased comity and greased the wheels of policymaking, influenced which congressmen attained institutional power, and eased the daily work life of those men who simply wanted to be popular amongst their peers. At the same time, this multitude of spatial restrictions, discursive slights, and everyday difficulties signaled to female legislators that they were not a natural element within congressional life. In the 1970s, the women’s movement would provide tools thatcongresswomen could use to challenge these social norms and gendered hierarchies. But through the 1960s, this masculine sociability, grounded in tradition, allowed men in Congress to retain power over what they perceived as their U.S. Congress and their legislative process.